Islamic Parenting Methods to Increase Resilience Capability in Foster Children at Bina Insani Orphanage, Moyudan, Sleman, Indonesia - Wahyuni, Puji; Zainuddin, Nurkhamimi (Journal of Islamic Education and Ethics, 2024)
Orphanages function as a substitute for families to meet children's needs during development. Foster children living in orphanages are vulnerable to resilience. Therefore, appropriate parenting methods are needed for children living in orphanages. This research aims to identify Islamic parenting methods to increase the resilience abilities of foster children because children living in orphanages are vulnerable to this. This research also analyzes the supporting and inhibiting factors in implementing Islamic parenting methods to increase the resilience abilities of foster children. This qualitative research used a descriptive approach. The data were collected through observation, interviews, and documentation. The validity of data was tested through triangulation of techniques and sources. Data analysis was carried out using descriptive analysis, namely reducing data, presenting data, and concluding data. The location of this research was at the Bina Insani Orphanage in Moyudan, Sleman. The respondents of this study were 3 caregivers and 4 foster children. This research found that: 1) Islamic parenting methods to improve the resilience abilities of foster children consist of the example method, habituation method, advice method, and attention method. 2) Supporting factors in implementing Islamic parenting methods to increase the resilience abilities of foster children consist of the role of administrators and teachers, the role of donors, and the available facilities and infrastructure. The inhibiting factors are a lack of awareness within the child, a lack of parenting cooperation between parents and guardians of the child and the orphanage, and negative effects from the external environment because foster children go to school outside the orphanage. Islamic parenting methods can be applied in educational institutions in the student's learning process to build good character and resilience. This research can be a basis for educational institutions to establish close collaboration with families in implementing Islamic parenting patterns.